Preservation and Accessibility of Audio-visual Records in Tanzania ’ s Television Broadcasting Companies - Komba, Shanel C; Nawe, J; Manda, P A (University of Dar es Salaam Library Journal, 2018)
This study investigated the preservation and accessibility of audio-visual records in television broadcasting companies in Tanzania. Specifically, it set out to determine how audio-visual records are preserved in television broadcasting companies; to establish how audio-visual records in television broadcasting companies in Tanzania are accessed and to examine challenges to effective preservation and accessing of audio-visual records in television broadcasting companies in Tanzania. The literature reviewed and the findings from pilot study indicate that many AV records are produced by individuals, television companies and other entities in both rural and urban Tanzania. They also indicate that there are intervening factors such as resource constraints, technological incompatibility, inadequate infrastructure, inadequate skills, environmental factors, and unclear policies the hinder access to and use of audio-visual records. Since the preservation and accessibility to audio-visual records is challenging due to intervening factors, it is recommended that approaches used (passive preservation and active preservation) to preserve audio-visual records be constantly reviewed to identify strategies that could be used to address challenges as they arise in order to improve preservation and accessibility of the relevant records.